Globalization and the national security state - Paul, T. V.; Ripsman, Norrin M. (New York ; Oxford : Oxford University Press, 2010)
In the past two decades, many have posited a correlation between the spread of globalization and the decline of the nation-state. They have maintained that the increasing interdependence between countries means that nations are no longer the sole providers of their territorial security. This text investigates.
Includes bibliographical references and index.
Description based on print version record.
Keywords: National security; Nation-state and globalization